Serotyping of Chlamydia I. Isolates of Ovine Origin - Schachter, Julius (1974)
Eight chlamydial isolates of ovine origin were tested in a plaque reduction system using homologous and heterologous rooster antisera. The eight isolates could be separated into two separate immunotypes. Type 1 included isolates associated with ovine abortion and one agent recovered from the feces of an apparently normal sheep. Type 2 isolates were associated with polyarthritis and conjunctivitis. These two serotypes were not cross-reactive with several chlamydiae of avian origin. Further application of the plaque reduction test may provide a useful means of typing chlamydiae.